ANALISIS PROGRAM PAMSIMAS (PENYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT) BERBASIS SUSTAINABLE DEVELOPMENT GOALs DI DESA MEKARWANGI - Erlinda, Titeu; MPA, TATI; Kristian, Indra; Fatmawati, Fatmawati (Jurnal Identitas, 2023)
The program implemented by the government to increase the supply of clean water is the Community-Based Water Supply and Sanitation Provision (Pamsimas) program, which aims to increase the population's coverage of proper and sustainable drinking water and sanitation services. PAMSIMAS (Community-Based Water Supply and Sanitation) is a government program that aims to create clean and healthy living communities by increasing access to sustainable drinking water and sanitation and actively involving the community through the Provision of drinking water and sanitation-based water supply and sanitation programs. community which is a commitment to continue the success of achieving the target of the Sustainable Development Goals (SDGs) program. This study uses qualitative research through interviews, observation and documentation. The interview technique used in this research is in-depth interview technique in the form of semi-structured interviews, to 8 informants. The results of this study were seen from the successful implementation of the PAMSIMAS program in Mekarwangi Village by applying sustainable indicators which included aspects of ecological, economic, socio-cultural, political, security and defense indicators.